2019
DOI: 10.3390/educsci9030191
|View full text |Cite
|
Sign up to set email alerts
|

Study Approaches in Higher Education Mathematics: Investigating the Statistical Behaviour of an Instrument Translated into Norwegian

Abstract: The revised two-factor study process questionnaire (R-SPQ-2F) has widely been considered valid and reliable in many contexts for measuring students’ learning approaches. However, its cultural specificity has generated considerable discussion, with inconclusive results when translated to different languages. This paper provides more insights into the construct validity of a Norwegian version of this instrument. The R-SPQ-2F is composed of ten items designed to expose deep learning approaches and 10 items design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 25 publications
4
34
0
3
Order By: Relevance
“…The model fits were assessed using selected goodness of fits (GOF) indices such as Tucker Lewis index (TLI), comparative fit index (CFI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR). These GOF indices were used because of the several empirical studies that have demonstrated their satisfactory fitting performance, e.g., (Zakariya 2019). Given the large sample size involved in the current study, the chi-square statistic was not used to assess the model fits directly because of its tendency to reject an acceptable model in the presence of a large sample size (Chen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The model fits were assessed using selected goodness of fits (GOF) indices such as Tucker Lewis index (TLI), comparative fit index (CFI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR). These GOF indices were used because of the several empirical studies that have demonstrated their satisfactory fitting performance, e.g., (Zakariya 2019). Given the large sample size involved in the current study, the chi-square statistic was not used to assess the model fits directly because of its tendency to reject an acceptable model in the presence of a large sample size (Chen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This version is a 19-item instrument that measures students' approaches to learning on a five-point Likert scale with 10 items measuring deep approach to learning and 9 items measuring surface approach to learning mathematics. The psychometric properties of this instrument were investigated elsewehere [54,55], and its reliability was found to be appropriate from 0.72 to 0.81 using Raykov and Marcoulides' [56] formula.…”
Section: Methodsmentioning
confidence: 99%
“…There are different studies where the Biggs questionnaire has been used to evaluate students' approaches to learning and its effectiveness has been evaluated in different sociocultural contexts. In fact, the R-SPQ-2F questionnaire has been adapted to several languages [27,32,61,[77][78][79][80][81] and it has been tested in a varied range of contexts. For example, in medical studies, students showed mostly an approach to deep learning in Ghana [32] or Saudi Arabia [82] and similar results were obtained in Malaysia in business, computer, and engineering programs [83].…”
Section: Literature Reviewmentioning
confidence: 99%